Implementasi Hukum Pencemaran Nama Baik di Indonesia dan Amerika Serikat: Sebuah Studi Komparatif - Kamila, Fildza Nazhifah; Hakim, Muhammad Firman; Andika, Nur Dwi; Suyudi, Saskia Mediana Putri; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This comparative legal study examines the civil defamation frameworks of Indonesia and the United States by analyzing two prominent defamation cases: Amber Heard v. Johnny Depp in the United States and Pemuda Panca Marga v. Tempo in Indonesia. These cases highlight the contrasting legal principles and cultural approaches to protecting reputation and freedom of expression within different legal systems. The United States, under its common law system and First Amendment protections, places a high burden of proof on public figures, requiring evidence of actual malice to succeed in a defamation claim. In Depp v. Heard, the court sided with Depp, reflecting a nuanced application of defamation law even amidst high public scrutiny and media influence. Conversely, Indonesia adheres to a civil law system, where defamation is addressed as an unlawful act under Article 1365 of the Indonesian Civil Code. In Pemuda Panca Marga v. Tempo, the organization sued a media outlet for reputational damage, and the case illustrates how Indonesian courts may interpret harm to collective reputation and public image under civil law provisions. This study reveals that while the U.S. legal system emphasizes the protection of public discourse and freedom of the press, the Indonesian approach tends to prioritize reputational protection, particularly when institutions or organizations are involved. The findings suggest the need for a balanced legal framework in Indonesia—one that safeguards reputation without compromising the principles of free expression in a democratic society.